Acercamiento teórico a la constitucionalidad del sistema tributario colombiano (2021)
This reflection article is the result of the research project "Social perception of small taxpayers about the constitutionality of the Colombian tax system", which general objective is to analyze the social perception of small taxpayers about the constitutionality of the Colombian tax system. The research is carried out from a qualitative approach and from a documentary study strategy. The results show the constitutional basis for the payment of the Colombian tax and how this is materialized in the tax system, which makes it a changing system. As conclusions it is possible to visualize the guarantee of the tax from the constitution, the realization of the purposes of the State with its collection and the power to demand the payment of fair tax under the constitutional framework.